PERSEPSI MASYARAKAT TENTANG PENGELOLAAN TEMPAT PEMAKAMAN UMUM (Studi Pada Keterbatasan Lahan Pemakaman Umum di Kota Pekanbaru) - Utama, Yunita; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in the city of Pekanbaru. The purpose of this research is to know the effort of the management of the cemetery in the city of Pekanbaru. Topic the focus of this research is to know the public perception about the limitations of the land of the cemetery in the city of Pekanbaru. The sample in this study amounts to 10 people. The author uses qualitative methods and sampling techniques the taking of pusposive. Data instruments are observation, interview and documentation. From the research that is done, the author finds that any existing Public Cemeteries in the city of Pekanbaru is in compliance with the required. As well as the existence of road access is provided at every Public Cemetery. Each Public Cemeteries to pay for family buried in the General Cemetery. In Public Cemeteries have billboards which proclaim the status of ownership of Public Cemeteries. Adagotong not work together to open up new land burial. While mutual clearing tomb was usually done when welcoming the fasting month Idul fitri holiday or good government-run, as well as the community. Based on research, it was found that the existence of the review conducted by the Government on each cemetery and not to the cemetery maintained by the people. Nothing as well as the existence of sosialitation about the funeral.Keywords: Perception, Urban, Public Cemetery